Prevalence and application of priming exercise in high performance sport. Issue 3 (March 2020) - Harrison, Peter W.; James, Lachlan P.; McGuigan, Mike R.; Jenkins, David G.; Kelly, Vincent G.
Abstract: Objectives: Recent research has revealed that low volume resistance 'priming' exercise may improve neuromuscular performance when completed within 48 h before competition. The aim of this study was to investigate the current prevalence and application of this strategy by practitioners in sport. Design: This study surveyed practitioners who were currently programming and/or prescribing resistance training programs for high performance athletes. Methods: Sixty-nine practitioners completed the online survey relating to their perceptions of resistance priming exercise strategies and the training methods prescribed in the days prior to competition. Results: Fifty-one percent of respondents currently prescribed priming exercise. Of the practitioners who prescribed this strategy, most respondents (59%) prescribed this session within 8 h of competition. Sessions typically included 2–3 upper body and lower body exercises (mean = 2.5 ± 0.7 and 2.1 ± 0.6 respectively), usually involving both loaded and unloaded activities. Large variations in exercise selection were reported, however, unloaded jumps (87%), loaded jumps (60%) and bench press (56%) were commonly prescribed. A low volume of sets (mean = 2.8 ± 0.9) and repetitions (mean = 3.8 ± 1.3) were used during these sessions. Lastly, various resistance loading strategies were prescribed, ranging from unloaded activities to heavy loaded exercises performed at ≥85% 1RM. Conclusions: Priming exercise is currently prescribed by many practitioners to prepare athletes for competition. A wide range of priming exercise methods are used, despite limited evidence supporting these methods. Future research should examine the effects of the various priming methods which are currently applied in practice.